Serum ?-carotene and Vitamin A Levels in Calves with Amaurosis - Gul, Yusuf; Issi, Mustafa (Kafkas Univ, Veteriner Fakultesi Dergisi, 2011)
In the present study, different breed, ages and sex 40 calves with clinically amaurosis was used. After clinical examination of the calves, were made analysis of sera beta-carotene and vitamin A levels as spectrophotometric. The mean beta-carotene and vitamin A levels were determined as 6.36 +/- 4.1 mu g/dL and 6.55+1.9 mu g/dL, respectively. As a result, it should be considering of particularly hypovitaminosis A in calves with amaurosis.
Amorozisli Buza?ıların Kan Serumlarında ?-Karoten ve A Vitamini Düzeyleri
Keywords: Amaurosis; Calf; beta-Caroten; Vitamin A; Hypovitaminosis A